A rare case of uterus didelphys presented as secondary abdominal pregnancy - Gupta, Neena; Gupta, Sachidanand; Singh, Neetu; Arya, Arun Kumar; Lal, Pavika; Chauhan, Monica (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Uterus didelphys is a rare type of uterine malformation with poor obstetric outcome. We report a rare case of ruptured uterus didelphys presenting as secondary abdominal pregnancy which was managed by removal of ruptured uterus along with the omentum to which placenta was attached. There should be a high degree of suspicion for proper management of such cases as these patients carry great morbidity and mortality if left undiagnosed and untreated.